International marketing research - Kumar, V. (Upper Saddle River, N.J. : Prentice Hall, 2000)
The nature and scope of international marketing research. Marketing research in the international environment. International marketing research process. Preliminary stages of the research process. Secondary data research. Marketing research on the internet. Primary data research. Qualitative and observational research. Survey research. Scale development. Questionnaire design. Sampling. Simple data analysis. Advanced data analysis. Multivariate data analysis. Presenting the results. Asia-Pacific. Europe. Latin America. Middle East and Africa. North America. The future of International marketing research.
Keywords: Marketing; Export marketing; Export marketing